Harmful algae of Malaysia - Mohammad Noor, Normawaty; Moestrup, Ojvind; Leaw, Chui Pin; Lim, Po Teen; Chin, Grace Joy Wei Lie; Usup, Gires (IIUM Press, International Islamic University Malaysia, 2018)
Harmful Algal Bloom (HAB) is a natural phenomenon that has been reported all over the world including in Malaysia. The impact of this event to the human health, economy and tourism industry can be devastated depending on the scale. In Malaysia, HAB cases have been reported since the past decade. Since then, more and more cases were reported covering different geographical areas. This book provides a description of a list of HAB species that has been reported in Malaysia together with colourful photomicrographs, newspaper cutting reporting the event, collection method and its impact. This essential information is a must-know knowledge for those who works on algae especially HAB.